Effect of different interlayers on microstructure and mechanical properties of diffusion-bonded joints between SiC and 316LN. Issue 2 (17th January 2022) - Huang, Bensheng; Shu, Zhihang; Li, Tianning; Li, Hao; Zhang, Dongyu; Yi, Feng
ABSTRACT: To study diffusion bonding between dissimilar materials of SiC ceramic and 316LN stainless steel, a bonded joint was prepared using vacuum solid-phase diffusion. At high temperatures, chemical and thermomechanical incompatibilities exist between SiC and 316LN, and the coefficients of thermal expansion of both SiC and 316LN are different. This results in a large residual stress in the joint, and therefore, direct bonding between SiC and 316LN is unsuccessful. Therefore, to decrease the residual stress and improve the joint quality and strength, Mo, Mo/Cu, and Mo/Ni/Cu/Ni layers are used as interlayers. Microstructural observations and shear strength analyses indicate that the SiC/316LN joint with Mo/Ni/Cu/Ni as the middle layer exhibited good interface bonding. The shear strength of the joint increases, up to 27.1 ± 3.4 MPa. Brittle fracture failure is located at the side of the SiC.